Analysis of Public Administration Ethics in the Implementation of the Electronic-Based Government System (SPBE) in the Regional Government of Gorontalo City - Auralia Davina Salsabila; Raihan A. Hanasi; Vanisa Andira Bawole; Sri Junianti Labadjo; Nur Anisa Katili; Nur Alyanti Ibrahim (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
This study aims to analyze public administration ethics in the implementation of the Electronic-Based Government System (SPBE) in the Regional Government of Gorontalo City. The research uses a qualitative method with a descriptive approach through data collection techniques in the form of literature studies by utilizing various reference sources, such as books, scientific journals, official documents, academic articles, as well as laws and regulations related to the Electronic-Based Government System (SPBE) and public administration ethics. The results showed that the implementation of SPBE in Gorontalo City has been supported by regional regulations and national policies, but its implementation still faces obstacles in aspects of system integration, human resource competence, public digital literacy, and the application of public service ethics. This study also found that the success of SPBE is not only influenced by technological readiness, but also by the quality of bureaucratic governance, transparency, accountability, and the professionalism of government officials in providing services to the community. Therefore, strengthening public administration ethics is an important factor in supporting the effectiveness of electronic-based government services.